MODEL PENGUATAN KARAKTER GENERASI MUDA BERBASIS NILAI KEISLAMAN DAN KEARIFAN LOKAL DI NAGARI SANDI ULAKAN - Joni Indra Wandi; Aulia Fitri; Cipto Duwi Priyono; Sumiari Sumiarti; Arief Arafat Hankam; Nora Afnita (Institut Agama Islam Sumatera Barat, 2026)
Strengthening the character of young people has become an increasingly important agenda amid rapid social change, technological advancement, and the declining involvement of adolescents in religious and local cultural activities. Nagari Sandi Ulakan, a community that continues to preserve Islamic traditions and local wisdom, provides a strategic setting for character education based on community engagement. This community service program aimed to strengthen Islamic values and youth character through a participatory approach that integrated religious education, local wisdom, and community empowerment within the framework of the Community Service Program (Kuliah Kerja Nyata—KKN). The program employed a Participatory Action Research (PAR) approach consisting of community needs assessment, program planning, implementation, mentoring, and participatory evaluation. The activities included Qur’anic learning at Islamic learning centers, congregational prayers, religious lectures, Islamic knowledge competitions, Fahmil Qur’an, grand religious gatherings, environmental education, community clean-up activities, and youth participation in local religious and cultural traditions. The findings indicated increased youth participation in religious activities, stronger social responsibility, greater environmental awareness, enhanced cooperation through communal work, and improved understanding of local Islamic history and cultural values. In addition, the program contributed to the development of students’ leadership, communication, and collaborative skills through direct engagement with community members. The results suggest that integrating Islamic values with local wisdom provides an effective and sustainable strategy for character development that is culturally relevant and socially responsive. This model may serve as a practical reference for community-based character education programs in other regions with similar socio-cultural contexts